Analisis Kemampuan Keuangan Daerah Dan Trend Provinsi Sumatera Selatan - Annisa Salsabila; Intan Sania; Sulistia; Agung Rizki Putra (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This research aims to determine the financial capacity of the Regional Government of South Sumatra Province for the 2017-2023 Fiscal Year as seen from the ratio of effectiveness, efficiency, Routine Capability Index (IKR), and trend analysis. This research is quantitative descriptive. The data collected in this study was obtained through documentation methods which were then analyzed through descriptive analysis. This research indicates that in South Sumatra Province, the PAD effectiveness ratio is included in the quite effective category, the efficiency ratio is included in the very efficient category, the routine capability index ratio is included in the very poor category, and the effectiveness trend shows a negative direction of development as well as The trend of the Routine Capability Index (IKR) shows a negative direction of development. Meanwhile, the efficiency trend shows a positive direction of development.